Cryptosporidium Infection in Pre-Weaned Ruminants and Pigs in Southwestern Nigeria (Global Journal of Medical Research, 2014)
The study was carried out to detect Cryptosporidium coproantigens in pre-weaned ruminants and pigs in Ogun State, southwestern Nigeria. Faecal samples of 186 pre-weaned animals comprising calves (n=32), lambs (n=47), goat kids (n=36) and piglets (n=71) were collected and examined for Cryptosporidium antigens by the use of an enzyme-linked immunosorbent assay (ELISA). 60.2% (112/186) of the samples were positive for Cryptosporidium antigens with infection rates of 78.1% (25/32), 51.1% (24/47), 83.3% (30/36) and 46.5% (33/71) for calves, lambs, goat kids and piglets respectively. The infection rates among animal species sampled were significantly different (p
Keywords: cryptosporidium; ELISA; nigeria; pre-weaned animals